Macrophage subpopulations in lamina propria of normal and inflamed colon and terminal ileum. Issue 6 (June 1989) - Mahida, Y R; Patel, S; Gionchetti, P; Vaux, D; Jewell, D P
Abstract : The aim of this study was to characterise human intestinal macrophages in normal and inflamed ileum and colon. Immunoperoxidase staining with a panel of monoclonal antibodies and histochemical staining for acid phosphatase and non-specific esterase was performed. In the superficial lamina propria, normal colonic macrophages were larger and more strongly positive for acid phosphatase and non-specific esterase than those in normal terminal ileum. There were more macrophages staining with monoclonal antibody RFD1 in the superficial lamina propria of the latter. Studies in inflammatory bowel disease tissue showed the presence of macrophages staining with monoclonal antibodies RFD9 and 3G8 which were rarely present in normal tissue and represented a different pattern from that seen in infectious colitis. Studies on isolated intestinal macrophages confirmed the findings in tissue sections. Subpopulations of intestinal macrophages are likely to have different functional roles. Phenotypic changes during inflammation may be induced by mediators of inflammation or may represent a recently recruited population of cells.